Lung Ultrasound Utility in the Management of the Neurologically Deceased Organ Donor. (September 2016) - Lebovitz, Daniel J.; Tabbut, Matthew; Latifi, Samir Q.; Dezelon, Lynn; Jones, Robert
Context: Lung transplantation is limited by donor lung availability with ∼20% of deceased donor lungs transplanted. Diagnostic testing identifying pulmonary derangements guide donor management strategies to maximize lung transplantation. Lung ultrasound (LUS) identifies pathology in critically ill patients equivalent or superior to chest radiograph (CXR) or computed tomography (CT) scans. No published studies have reported on LUS in neurologically deceased donors (DNDDs). Objective: We evaluated LUS in identifying abnormal lung pathology in DNDDs and related these findings to the standard approach. Design: Prospective pilot study. Setting: Intensive care units, university-associated teaching hospital. Participants: Six DNDDs evaluated during donor management. Interventions: Deceased donors were enrolled based on the availability of ultrasound operators (USOs). Bedside LUS was performed using Lichtenstein 3- or Volpicelli 4-zone method based on the operator preference. Lungs were evaluated for sliding, A/B profile, consolidation, or pleural fluid. Ultrasound operators were blinded to donor management data. Lung ultrasound interpretations were compared for interindividual variability. Ultrasound and anteroposterior portable CXR (AP-CXR) results were compared by Organ Procurement Organization medical directors. Measurements and Main Results: Bedside LUS compared well to AP-CXRs during donor management. There was no interindividual variability noted among USOs. Lung ultrasound identified all findings on AP-CXR and additional clinical pathology not reported on AP-CXR. Reports on AP-CXRs took a median 202 (13-696) minutes to occur, with LUS results available immediately. Conclusions: Lung ultrasound may play a significant role in donor management providing real-time clinical data, allowing for rapid identification of abnormalities, and leading to management interventions that may increase the number of transplanted lungs.